Pengaruh Net Profit Margin Dan Return on Equity Tehadap Return Saham Pada Industri Property Dan Real Estate Di Bursa Efek Indonesia Periode 2012-2017 - Noni Indah Pratiwi (Universitas Batanghari Jambi, 2019)
As for the purpose of this research is to know, describe and analyzing the Influence of Net Profit Margin and Return On Equity on Return Saham on Industri Property and Real Estate Listed on Bursa Efek Indonesian (BEI) Period 2012-2017. The method used in this research is the study of literature’s, a study conducted by using literarure and writer’s that is closely related to the object of study, which is intended to obtain studid. Besides theory and information sourced from the internet. Based on the results of the regression analysis abowed that the regression equation Y = 8,688 + 0,322X1 + 0,968X2 + e, with R square 0,663. Partially the Return On Equity (ROE) of Return Saham on Industri Property and Real Estate Listed On Bursa Efek Indonesian (BEI) Period 2012-2017, with value of 2,083 and significant levels 0,044. Simultaneously there is an influence between the Net Profit Margin and Return On Equity on Return Saham. This is indicated by comparing Fhitung lebih besar dari Ftabel (3,790 > 3,295), and by comparing the magnitude of the significant number of research with the level of significant 0,05, then 0.0,31 < 0,05.